Some considerations on rawls and self-respect - Jungmann de Castro , Rodrigo (Kalágatos, 2021)
While agreeing with Rawls as concerns the principles of justice proposed in A Theory of Justice , I argue in this essay that neither these principles by themselves nor the more specific recommendations offered by Rawls provide a firm enough basis for the self-respect of society’s least well-off members, because Rawls pays insufficient attention to the symbolic dimension underlying the advertisement and promotion of luxury goods , the possession of which is systematically portrayed as having a bearing on the personal value of those who enjoy them.